2002
DOI: 10.1073/pnas.042680999
|View full text |Cite
|
Sign up to set email alerts
|

The first linkage disequilibrium (LD) maps: Delineation of hot and cold blocks by diplotype analysis

Abstract: Linkage disequilibrium (LD) provides information about positional cloning, linkage, and evolution that cannot be inferred from other evidence, even when a correct sequence and a linkage map based on more than a handful of families become available. We present theory to construct an LD map for which distances are additive and population-specific maps are expected to be approximately proportional. For this purpose, there is only a modest difference in relative efficiency of haplotypes and diplotypes: resolving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
168
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(170 citation statements)
references
References 32 publications
1
168
0
1
Order By: Relevance
“…Blocks of LD (SNPs with the same LDU location) represent areas of conserved LD and low haplotype diversity, and steps (increasing LDU distances) define LD breakdown, primarily caused by recombination, since crossover profiles agree precisely with the corresponding LDU steps. 16 The maps show numerous short blocks across the entire region with total LDU length being greater for AA (greater LD breakdown) than the EUR population. The functional location estimates A and E (13 kb apart) indicated by the vertical solid line arrows are associated with T2D in AA and EUR samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocks of LD (SNPs with the same LDU location) represent areas of conserved LD and low haplotype diversity, and steps (increasing LDU distances) define LD breakdown, primarily caused by recombination, since crossover profiles agree precisely with the corresponding LDU steps. 16 The maps show numerous short blocks across the entire region with total LDU length being greater for AA (greater LD breakdown) than the EUR population. The functional location estimates A and E (13 kb apart) indicated by the vertical solid line arrows are associated with T2D in AA and EUR samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…15 We constructed two highresolution genetic maps based upon HapMap data with genetic distances expressed in linkage disequilibrium units (LDU). 16 The EUR LDU map was used for analyses of the two EUR T2D datasets and the AA LDU map was used for the analysis of the AA T2D dataset. The autosomal genome (sex chromosomes were not included in the analyses) was divided into 4,800 non-overlapping analytical windows, each with a minimum distance of 10 LDU.…”
Section: Methodsmentioning
confidence: 99%
“…A number of recent studies of LD have shown that its distribution is not homogeneous across the genome. [33][34][35][36][37][38][39] The general pattern found in the regions examined so far is a series of discrete tracts of low recombination, high LD and therefore with a reduced number of haplotypes, the so-called 'haplotype blocks' bounded by recombination hotspots. Haplotype block structure has been found to vary according to genomic region (due to genomic factors affecting its pattern) and also between different global populations (due to demographic factors), 33,36,[38][39][40][41][42][43][44] see Bertranpetit et al 45 for a review.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Furthermore, there can be remarkable differences in the extent of association from one genomic region to another, 11 reflecting the location of recombination hot spots which generates a pattern of blocks of conserved LD and steps where LD breaks down. 12,13 Ohashi et al 14 showed that one of the major difficulties in testing association in case-control association studies is attributable to the large number of SNPs that must be used. In fact, a marked reduction in the statistical power of LD studies arises from multiple testing and the extremely low P-values required after Bonferroni adjustment, which are unlikely to be achievable with realistic sample sizes.…”
Section: Introductionmentioning
confidence: 99%